MADRASAH PRINCIPAL’S STRATEGY IN IMPROVING TEACHER PERFORMANCE AT MIN 1 ACEH JAYA - Supran (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Strategy is the process of designing, formulating, implementing, and evaluating the achievements made by the leadership of an institution towards improving the performance of subordinates in order to improve the quality of learning. Departing from the above understanding, the author wants to explore the strategies implemented by the head of MIN 1 Aceh Jaya in improving teacher performance, as well as how to avaluate their achievements.This research aims to; 1) expain the strategy of the madrasah head in improving teacher performance at MIN 1 Aceh Jaya. 2) describes the process of evaluating the achievement of the madrasah principal’s strategy in improving teacher performance at MIN 1 Aceh Jaya.The approach used in this research are a case study approach, namely in the form of events. issues, phenomena, processes, activities, programs, organizations, places, individuals and groups. The type is qualitative research by describing phenomena that occur that is relevant to the truth.The results of this study can be described as follows: 1) the madrasah head’s strategy in improving teacher performance at MIN 1 Aceh Jaya is to carry out continuous coaching, provide motivation, reward, maintain teacher discipline, evaluate and supervise teachers, conduct training, activating KKG, and sending teachers to training places. 2) in order to evaluate the achievement of the strategy the head of the madrasah assesses each individual teacher what achivements have been achieved and aspects that need to be improved. Then also the result of the “teacher performance test” become the basic reference in evaluating the achievement of improving teacher performance.